2020
DOI: 10.1097/tp.0000000000003157
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neighborhood-level Socioeconomic Deprivation and the Medication Level Variability Index for Children Following Liver Transplantation

Abstract: Background: Neighborhood socioeconomic deprivation is associated with adverse health outcomes. We sought to determine if neighborhood socioeconomic deprivation was associated with adherence to immunosuppressive medications after liver transplantation. Methods:We conducted a secondary analysis of a multicenter, prospective cohort of children enrolled in the Medication Adherence in children who had a Liver Transplant study (enrollment 2010-2013). Participants (N=271) received a liver transplant ≥1 year prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 58 publications
5
80
0
Order By: Relevance
“…Low socioeconomic status creates a milieu of overlapping barriers that negatively affect long‐term well‐being, such as inadequate nutrition, cost‐related medication underuse, impeded access to medication, fewer learning experiences, housing instability, unemployment, and lack of appropriate social networking, to name just a few 21‐23 . As in our study, Wadhwani et al demonstrated that children from deprived neighborhoods who undergo liver transplantation had worse patient and allograft survival 24 .…”
Section: Discussionsupporting
confidence: 64%
“…Low socioeconomic status creates a milieu of overlapping barriers that negatively affect long‐term well‐being, such as inadequate nutrition, cost‐related medication underuse, impeded access to medication, fewer learning experiences, housing instability, unemployment, and lack of appropriate social networking, to name just a few 21‐23 . As in our study, Wadhwani et al demonstrated that children from deprived neighborhoods who undergo liver transplantation had worse patient and allograft survival 24 .…”
Section: Discussionsupporting
confidence: 64%
“…Such geographic, place‐based data are associated with adverse health outcomes across diseases, and this knowledge has been used to improve other medical outcomes for children of low SES . Using a validated index of neighborhood socioeconomic deprivation in a cohort of pediatric liver transplant recipients, we previously demonstrated that children from the most deprived neighborhoods have twice the rates of nonadherence . This index, available for every US census tract and ZIP code, incorporates 6 measures of neighborhood SES from the US Census Bureau/American Community Survey.…”
Section: Introductionmentioning
confidence: 99%
“…52 In the United States as well, neighborhood social deprivation also correlated with nonadherence to immunosuppressive medications, a determinant of suboptimal long-term outcomes. 53 Our data were taken from the STCS, a nationwide prospective cohort study including over 95% of patients transplanted in 6 Swiss transplant centers. 39,40 Findings are generalizable for Switzerland, but not necessarily for other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomically deprived regions in England were also home to more chronic and end‐stage kidney disease 52 . In the United States as well, neighborhood social deprivation also correlated with nonadherence to immunosuppressive medications, a determinant of suboptimal long‐term outcomes 53 …”
Section: Discussionmentioning
confidence: 99%